DIAGNOSTIC IMAGING OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE: A TEN YEARS SYSTEMATIC REVIEW - Hayati, Rezeki; Candra, Rian (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Exacerbations of chronic obstructive pulmonary disease (COPD) impose a great burden on patients’ quality of life and healthcare systems. In addition to causing significant increases in mortality and disease progression, exacerbations of COPD amount to $18 billion in direct costs annually, as well as further spending associated with care and losses in productivity. Newer modalities such as OCT and MRI have distinct advantages to CT in such areas as image resolution and functional assessment of lung tissue. The aim: The aim of this study to show about diagnostic imaging of chronic obstructive pulmonary disease. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 100 articles, whereas the results of our search on SagePub get 1608 articles, on Google Scholar 3870 articles. Records remove before screening are 4887, so we get 691 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Imaging and image analysis offers new insight into pulmonary disease processes that were previously available only on tissue necropsy. Current techniques can offer detailed measures of lung structure and with newer modalities previously immeasurable things like regional lung function. Imaging in the context of clinical investigation may offer the ability to define more homogeneous subsets of subjects with COPD and to potentially provide an intermediate biomarker of disease progression in lieu of a declining FEV.